Pengaruh Penerapan Nilai-Nilai Islam, Citra Perusahaan Dan Kepuasan Nasabah Terhadap Loyalitas Nasabah Pada Bank Syariah Indonesia Di Kabupaten Bondowoso: The Influence of the Implementation of Islamic Values, Corporate Image and Customer Satisfaction on Customer Loyalty at Bank Syariah Indonesia in Bondowoso Regency - Lidia, Devi; Wulandari, Deasy; Suparman, Suparman (IJABAH: Indonesian Journal of Sharia Economics, Business, and Halal Studies, 2024)
This study seeks to evaluate the impact of applying Islamic values, the company's image, and customer satisfaction on customer loyalty in sharia banks located in Bondowoso Regency. The research is explanatory, focusing on the relationship or influence between independent and dependent variables. It employs a quantitative approach, sampling 100 Muslim customers of Indonesian sharia banks. Data collection was conducted via questionnaires distributed through Google Forms. The data were analyzed using multiple linear regression analysis, with the results derived from regression tests. The findings revealed that, firstly, the application of Islamic values does not independently affect customer loyalty. Secondly, the company's image has a partial impact on customer loyalty. Thirdly, customer satisfaction influences customer loyalty. Finally, the combined application of Islamic values, company image, and customer satisfaction has a significant effect on customer loyalty.